Recognizing farmers' knowledge in development initiatives: Indigenous bee-keeping in Alaba Special Woreda, Southern Ethiopia - Shiferaw, A.; Dindamo, B.; Berhe, Kahsay; Tegegne, Azage; Hoekstra, Dirk (ELDIS, 2008)
Woreda agriculture and rural development (OoARD) strategic plan identify honey as one of the priority commodities of the woreda. The OoARD and development partners are exerting effort to boost honey production by introducing modern bee-keeping practice. The success of current development effort in apiculture, to improve the living standard of low income farmers, is dependent on indigenous knowledge because it is the cultural base and starting point of the practice. Thus, recognizing and documenting indigenous beekeeping practice in the woreda is a pre-requisite to sustain honey production and strengthen existing development effort. This paper documents history of bee-keeping the social, medicinal and economic value of honey in Southern Ethiopia, Alaba special woreda. It examines features of indigenous bee-keeping practice and its link with modern bee-keeping in the study area. The study is based on group discussion, community ranking and key informants and household interview. Purposive sampling was used for PA selection from honey producing areas. Community data validation was undertaken at the end of the study. Findings show that knowledge of apiculture in Alaba originated from adjacent woreda and was adopted first in Besheno and surrounding area. Indigenous value of honey is reflected in the generations’ lore, its medical, economic and social value. Honey is used in various social events including conflict resolution, blessing, weeding and religious ceremony. The indigenous feature of beekeeping in Alaba and its value reflects the importance of apiculture and its cultural base for economic development. Early introduction of modern apiculture in the study area has not taken in to account the role and significance of indigenous knowledge in development process. On the bases of the findings, recommendations were suggested to integrate modern and indigenous apiculture development.